Digital Transformation in HR: Evaluating the Impact of Automation & AI on Employee Roles and Skill Requirements in Global Organizations - Mirsubhan, Mirza (My University, 2026)
The thesis deals with the analysis of how automation and AI affect human resources and labor roles in Azerbaijan and in globally to some extent. Human Capital Theory is used as a main framework to evaluate 317 respondents and five interviews with banking, transportation, ERP, railways, and public administration specialists. Outcomes demonstrate that automation reduces regular activities and accelerate strategic HR responsibilities. Digital literacy, analysis of data, adaptability are considered as more crucial. Moreover, the companies suggest activities that increases the learning abilities of workforce to create a protection for the employees. Even while there are global tendencies exist, Azerbaijan possesses it unique issues, such as senior workers who are unwilling to change, people who are not equally tech-savvy and so on. The thesis highlights that policymakers and organizations improve training, occupational standards, and inclusive adaptation techniques to retain worker competitiveness during digital change.
Keywords: Artificial intelligence -- Economic aspects.; Automation -- Social aspects.; Human capital.; Personnel management -- Technological innovations.; Labor market -- Effect of technological innovations on.; Technological innovations -- Economic aspects.